Tips and Tricks in the Laparoscopic Treatment of Type I Duodenal Atresia: Description of a Technique - Salvatore Fabio Chiarenza; Maria Luisa Conighi; Valeria Bucci; Cosimo Bleve (Children)
Introduction: Congenital duodenal atresia (DA) (Type I) with a fenestrated web can be characterized by a late presentation with a delayed diagnosis. It is even rarer and usually associated with proximal duodenomegaly. Conventional management involves web resection and duodeno–duodeno anastomosis with or without duodenoplasty. We describe our mininvasive surgical strategy and management, detailing the aspects of laparoscopic techniques. Material and Methods: We retrospectively reviewed the medical records of five patients affected by fenestrated duodenal web (DA) with a delayed onset of symptoms and diagnosis who were managed in our Department over a period of 10 years (2013–2023). We analyzed the age of patients at diagnosis, clinical signs and symptoms, associated congenital anomalies, radiological and intraoperative findings, surgical treatment, and outcomes. Diagnostic examinations included ultrasound (US), Upper-Gastrointestinal Study (UGI), and Esophagogastroduodenoscopy (EGDS). Results: Three boys and two girls, median age of 5.5 months (range 3–11 months), were included in this study. Three underwent previous surgery for long-gap esophageal atresia (EA), two of Type A, and one of Type C, requiring a gastrostomy immediately after birth (delayed esophageal repair for prematurity in Type C) and subsequent delayed primary anastomosis. Major associated anomalies were EA (3), anterior ectopic anus (1), cloaca (1), and Type IV laryngeal web (1). An antenatal diagnostic suspicion of duodenal atresia (obstruction) on ultrasound was described in two patients. UGI suggested a fenestrated duodenal web, visualized at ultrasound in two patients. Duodenal dilation was associated in two cases. The symptoms were feeding difficulties, nonbilious vomiting, upper abdominal distension, and poor growth. All presented with a pre-ampullary obstruction. Endoscopic confirmation was only possible in one patient. The older patient underwent an endoscopic resection of a duodenal web. In the other four, we performed a laparoscopic longitudinal antimesenteric duodenal incision, web resection (excision), and transverse suture (closure was performed) without duodenoplasty. Intraduodenal Indocyanine Green (ICG) visualization (under near-infrared light) was used in the last two cases. No postoperative complications were recorded, with a mean hospital stay of 8 days. A contrast study performed at 4 weeks demonstrated an improved proximal duodenal profile; patients tolerated a full diet and remained symptom-free. Conclusions: According to our experience with minimally invasive techniques, laparoscopy and endoscopy are effective and safe, supporting web resection for the management of a duodenal web without tapering of the proximal duodenum. They require advanced technical skills. Intraduodenal-ICG injection during laparoscopic treatment of Type 1 DA allows localization of the duodenal web, confirmation of bowel patency (bowel canalization) and the tightness of suture.